ANALISIS ASPEK GRAMATIKAL DAN ASPEK LEKSIKAL PUISI “PAPUA” KARYA FRANS P. PANDONI - Sitti Mariati (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Poetry as a discourse is arranged by grammatical and lexical aspects. Therefore, to know what grammatical and lexical aspects are used by the author in writing the poem "Papua", this study uses a method called the descriptive method. The grammatical aspects contained in the poem "Papua", namely referential (reference) consist of (1) reference persona (first person singular, first person singular bound form, second person singular, and second person singular bound form), (2) demonstrative reference and (3) comparative reference and coupling (conjunctions) and conjunctions (conjunctions) consist of addition conjunctions (additives) and causal conjunctions. The lexical aspects contained in the poem "Papua", namely repetition consist of epizeuksis repetitions and anaphora repetitions, synonym phrases with phrases, and absolute antonymy. Both of these aspects, grammatical and lexical aspects, are used by poets to compose word by word to produce a cohesive and coherent poetic text.